The Analysis Of Social And Emotional Development Of Mentally Disabled Children (Mild) On Grade 2 Of Muhammadiyah Banguntapan Primary School Yogyakarta - Assingkily, Muhammad Shaleh; Khoeriyah, Munganatul; Putro, Khamim Zarkasih (UIN Sunan Kalijaga Yogyakarta, 2019)
Every child is unique, including a mentally disabled child. The potential for self-development in academic, social, and workability becomes a necessity for mild mentally disabled children. This study aims to analyze the social and emotional development of mild mentally disabled children in grade 2 of Muhammadiyah Banguntapan Primary School Yogyakarta, or usually called SD Muhammadiyah Banguntapan Yogyakarta. Two formulations of the problems of this research are (1) how the social-emotional development of mild mentally disabled children in grade 2 of SD Muhammadiyah Banguntapan Yogyakarta in the classroom and outside the classroom and (2) how the teacher's efforts in developing the child's social-emotional development. The research data were obtained through a qualitative approach with observation, interviews, and analysis of document studies of mild mentally disabled children in grade 2 of SD Muhammadiyah Banguntapan Yogyakarta. From this study, the results were obtained that the social-emotional development of mentally disabled children in the class was achieved in the form of caring, interactive, and displaying an attitude of confidence, while what was not achieved in the form of participation, communication, and teamwork abilities. Whereas outside the classroom, the attainment is in the form of empathy and what is not achieved in the form of solitude and self-ness (ego) and has not been able to control emotions when socializing. The efforts made by teachers in developing children's social-emotional attitudes, namely: asking children to apologize and admit their own mistakes, motivating,